Nursing Supervision Model for Pressure Ulcer Prevention in Patients at Risk of Pressure Ulcers at King Taksin Memorial Hospital - Panuwatsuk, Manee; Tongchai, Prawit; Boonsut, Chayapak (Journal of The Royal Thai Army Nurses, 2025)
The aim of this study was to develop and evaluate a nursing supervision model for preventing pressure ulcers in at-risk patients at Taksin Hospital. The population consisted of 9 head nurses as supervisors and 142 professional nurses as supervisees. This participatory action research was conducted in three phases 1) Situation analysis, 2) Model development, and 3) Evaluation. Research instruments included semi-structured interview forms and a 24-item satisfaction assessment questionnaire using a 5-point rating scale. Data analysis was conducted using percentage, mean, standard deviation, and content analysis. The findings revealed that 1) The nursing supervision model for preventing pressure ulcers in at-risk patients at Taksin Hospital is termed the COMPASS Model, comprising five key elements Collaborative supervision, Multidisciplinary supervision, Proactive supervision, Technology-supported supervision, and Sustainable supervision. 2) Following implementation, both supervisors and supervisees reported good satisfaction levels ( = 3.85), with the highest satisfaction related to outcomes and sustainability, followed by content and technology application, and creative participatory supervision. The model is characterized by a clear systematic approach, encourages participation, fosters team-based learning, and enhances nurses’ skills and confidence in preventing pressure ulcers.